Cost-effectiveness analysis of rimegepant for on-demand acute treatment of migraine in China - Tian, Shuo; Yang, Yuping; Tan, Shenglan; Luo, Jiani; Yang, Chuanyu; Liu, Qiao; Guo, Yujin (Frontiers in Neurology, 2024)
Purpose: This study assesses the cost-effectiveness of rimegepant for the on-demand acute treatment of migraine in the Chinese population, focusing on headache relief within a 2-hour timeframe. Utilizing data from Phase III clinical trials on rimegepant involving Asian populations, this analysis aims to provide essential insights for healthcare decision-making in the context of migraine management in China. Patients and methods: Employing a decision tree model, this research evaluates the cost-effectiveness of rimegepant over a concise 2-hour period, exclusively considering its direct market price of 219.00 CNY per dose for on-demand, single-use treatment upon approval in China. This model is based on pain relief outcomes from a clinical trial, categorizing health outcomes by the achievement of pain freedom and alleviation from the most bothersome symptom within two hours post-administration. Results: The study unveils that rimegepant adds 0.0018 quality-adjusted life days (QALD) with an incremental cost-effectiveness ratio (ICER) of 122,166.07 CNY/QALD. Against a daily cost-effectiveness threshold derived from the 2023 per capita GDP of China (734.45 CNY/day), rimegepant falls short of proving its cost-effectiveness. A significant price reduction to approximately 1.32 CNY per dose is required for rimegepant to be considered cost-effective within this framework. Furthermore, a series of sensitivity analyses were conducted to validate the robustness of these results. Conclusion: While rimegepant shows clinical efficacy in providing rapid relief from migraine symptoms, its current pricing exceeds the threshold for cost-effectiveness in the Chinese healthcare setting. This study underscores the need for price adjustments to enhance the accessibility and economic viability of new migraine treatments.